Polyacrylamide-based organic / inorganic hybrid nanomaterial, fire-retardant pre-reaction liquid, and preparation method and application thereof

By using polyacrylamide-based organic/inorganic hybrid nanomaterials with a ‘super-shaped multi-layer core-shell structure to form an interpenetrating network structure with cellulose, the problem of poor UV radiation resistance performance of the existing flame retardant fire-resistant prereaction liquid is solved, and a high-performance fire-resistant glass coating is achieved.

CN119285872BActive Publication Date: 2025-04-18BEIJING UNIV OF CHEM TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411499260.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-04-18
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The existing flame retardant fire-proof prereaction liquid has poor UV radiation resistance, which causes the fire-proof layer to crack and fall off after long-term use outdoors, and has poor solvent resistance, hardness, low temperature resistance and impact resistance, which affects its use effect and life.

Method used

Using polyacrylamide-based organic/inorganic hybrid nanomaterials with a ‘supra’-like multilayer core-shell structure and multiple crosslinkable, a linear graft polymer is formed by introducing double bonds and amine groups on the surface of hydrophilic silica, and an interpenetrating network structure is formed with cellulose, thereby improving the crosslinking degree and weather resistance of the coating.

Benefits of technology

It significantly improves the UV radiation resistance, impact resistance, hardness and water flush resistance of the fireproof layer, extends its service life, and meets the flame retardant standards of DIN4102 B1 and UL94-V0.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285872B_ABST
    Figure CN119285872B_ABST
Patent Text Reader

Abstract

The present invention relates to a polyacrylamide-based organic / inorganic hybrid nanomaterial, a fireproof pre-reaction liquid and a preparation method and application thereof, wherein the polyacrylamide-based organic / inorganic hybrid nanomaterial includes polyacrylamide-based organic / inorganic composite latex particles, the latex particles include a flexible core layer, a functional shell layer and a reinforcing transition layer, and the reinforcing transition layer is arranged between the flexible core layer and the functional shell layer; the flexible core layer is polyacrylamide latex particles, the reinforcing transition layer is a polymer layer containing melamine formaldehyde material with a cross-linked network structure, and the functional shell layer is a polymer layer of a phosphorus-containing polymer and a silicon-containing polymer. The fireproof pre-reaction liquid in the present invention has the characteristics of low viscosity and can form an interpenetrating network structure with cellulose, can be coated on the surface of a transparent cellulose-modified soda-lime glass product to form a fireproof layer, and at the same time, the low-temperature use temperature can reach ‑25°C ± 1°C, and the coating is resistant to ultraviolet radiation for more than 2000 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of glass safety, and in particular to a polyacrylamide-based organic / inorganic hybrid nanomaterial having a "roxburgh"-shaped multilayer core-shell structure and capable of multiple crosslinking, a fireproof pre-reaction liquid, and a preparation method and application thereof. Background Art

[0002] As urbanization progresses at an increasingly rapid pace, the building windows of houses are becoming larger and larger. Elegant, beautiful, and functional glass components are gradually gaining favor among designers at home and abroad, which directly leads to the rapid development of various types of safety glass and special glass in the architectural glass industry. Architectural glass has gradually developed from being a simple lighting and decorative material to having multiple functions such as light control, room temperature regulation, noise reduction, and improvement of living environment. Special coatings have gradually developed from being a simple anti-corrosion and decorative material to having multiple functions such as flame retardancy, heat insulation, wear resistance, damping, and noise reduction.

[0003] As a safe coating, flame retardant fire-proof pre-reaction liquid has some properties of ordinary coatings, as well as the properties of controlling the spread of fire and heat insulation, which provides valuable rescue time for effective rescue in the event of a fire, minimizes the loss of personnel, property and vehicles, and reduces the destructive power of fire to a minimum. Fireproof glass can be formed by coating on the surface of glass. In addition to some properties of ordinary glass, coated fireproof glass can also protect escape and rescue personnel from heat radiation damage. Due to the recent frequent fires in some well-known large buildings at home and abroad, people have gradually begun to pay attention to the research and development, production and use of new flame retardant coatings. Poor resistance to ultraviolet radiation is one of the main factors restricting the application of flame retardant coatings. Therefore, it is an important direction for the industrialization of special coatings to develop high-performance flame retardant fire-proof pre-reaction liquids with excellent resistance to ultraviolet radiation, achieve a qualitative leap in product performance, and expand the application area of ​​products.

[0004] At present, the work done in China on flame-retardant fire-proof pre-reaction liquid for glass is at the basic research stage. The existing flame-retardant fire-proof pre-reaction liquid has poor resistance to ultraviolet radiation, and needs to be frequently applied regularly, with a large amount of fire-retardant coating. At the same time, most products will crack and fall off from the glass surface under long-term outdoor ultraviolet radiation, and cannot meet the requirements for long-term outdoor use in the rainy southern regions; the existing flame-retardant coating also has poor solvent resistance, hardness, low temperature resistance, and impact resistance, which reduces the actual fireproof effect of the fireproof layer and seriously affects the use effect and service life of the flame-retardant fire-proof pre-reaction liquid. Summary of the invention

[0005] The main purpose of the present invention is to provide a polyacrylamide-based organic / inorganic hybrid nanomaterial with a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking, a fire-proof pre-reaction liquid and a preparation method and application thereof, which overcomes the disadvantages of the fire-proof materials in the prior art that they cannot meet the ultraviolet test, and avoids the shortcomings of cracking of the fire-proof layer made of the fire-proof materials, mismatch between impact resistance and hardness, and poor weather resistance.

[0006] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.

[0007] Polyacrylamide-based organic / inorganic hybrid nanomaterials include polyacrylamide-based organic / inorganic composite latex particles, the polyacrylamide-based organic / inorganic composite latex particles include a flexible core layer, a functional shell layer and a reinforcing transition layer, the reinforcing transition layer is arranged between the flexible core layer and the functional shell layer; the functional shell layer is a polymer layer inlaid with surface-modified hydrophilic silica nanoparticles and containing phosphorus-containing polymers and silicon-containing polymers, and at least one of the polymers in the functional shell layer is a polymer that can form an interpenetrating network structure with cellulose, and in the functional shell layer, one end of linear ammonium polyphosphate and one end of linear polymethacrylate glycidyl are respectively grafted on the surface-modified hydrophilic silica nanoparticles, and the other end of the linear ammonium polyphosphate and the other end of the linear polymethacrylate glycidyl are respectively located outside the shell of the functional shell layer; the reinforcing transition layer is a polymer layer containing melamine formaldehyde material with a cross-linked network structure; the flexible core layer is polyacrylamide latex particles. In the present invention, both linear polymethacrylate glycidyl and linear ammonium polyphosphate can form an interpenetrating network structure with cellulose.

[0008] The polyacrylamide-based organic / inorganic hybrid nanomaterial is made of the following components: 10 to 25 parts by weight of a fourth mixed solution and 58 to 352 parts by weight of a third polymer template solution; the fourth mixed solution is made by mixing 5 to 15 parts by weight of glycidyl methacrylate, 0.01 to 0.2 parts by weight of an initiator and 5 to 10 parts by weight of deionized water; the third polymer template solution is made by 7 to 26 parts by weight of the third mixed solution and 51 to 326 parts by weight of a second polymer template emulsion; the third mixed solution is made by 5 to 15 parts by weight of ammonium polyphosphate, 0.5 to 1 parts by weight of ethanol and The second polymer template emulsion is made of 0.3-18 weight parts of the second mixed solution, 15-40 weight parts of deionized water, 10-26 weight parts of silicon dioxide dispersion with double bonds and amine groups on the surface, 0.003-0.03 weight parts of initiator, and 26-242 weight parts of the first polymer template emulsion; the second mixed solution is made of 0.1-6 weight parts of butyl acrylate, 0.1-6 weight parts of methyl methacrylate, 0.1-6 weight parts of methacrylic acid and 0.01-0.02 weight parts of reactive emulsifier. The first polymer template emulsion is made of 0.5-80 weight parts of the first mixed solution, 6-12 weight parts of deionized water, 0.005-1 weight parts of initiator and 20-150 weight parts of polyacrylamide emulsion with a particle size of 40nm-200nm and a solid content of 15wt%-55wt%; the first mixed solution is made of 0.1-20 weight parts of butyl acrylate, 0.1-20 weight parts of melamine, 0.1-20 weight parts of styrene, 0.01-0.03 weight parts of divinyl sulfone, 0.05-0.2 weight parts of 20wt% ammonia water, The invention discloses a method for preparing a hydrophilic silica dispersion liquid comprising: a silica seed solution having double bonds and amine groups on the surface of the silica dispersion liquid; a silica seed solution having a double bond and an amine group ... seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine group on the surface of the silica seed solution; a silica seed solution having a double bond and an amine

[0009] The polyacrylamide-based organic / inorganic hybrid nanomaterial has a polymerization degree of 10,000 to 100,000 polyacrylamide particles in the polyacrylamide emulsion, a particle size of 40 nm to 200 nm, and a single-peak narrow distribution of particle size.

[0010] In the polyacrylamide-based organic / inorganic hybrid nanomaterial, the alkenyl silane coupling agent is one or more of vinyl triperoxide tert-butyl silane, vinyl triethoxy silane, butadienyl triethoxy silane, vinyl trimethoxy silane, isobutylenyl triethoxy silane and vinyl tri(β-methoxyethoxy) silane; the amino silane coupling agent is one or more of one or more of the silanes selected from the group consisting of anilinomethyl triethoxy silane, γ-aminopropyl trimethoxy silane, N-β(aminoethyl)-γ-aminopropyl triethoxy silane and 3-aminopropyl triethoxy silane; and the initiator is one or both of a thermal initiator and a redox initiator.

[0011] The polyacrylamide-based organic / inorganic hybrid nanomaterial, the emulsifier is a reactive emulsifier.

[0012] The method for preparing the above polyacrylamide-based organic / inorganic hybrid nanomaterial comprises the following steps:

[0013] S11) preparing a silicon dioxide seed solution: mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3:0.02-0.04:8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm-30 nm;

[0014] S12) preparing a silica dispersion with double bonds and amine groups on the surface: placing a silica seed solution, an alkenyl silane coupling agent, an amino silane coupling agent and ethanol in a ratio of 10-25: 0.1-0.5: 0.1-0.5: 0.001-0.02 in a high-pressure homogenizer for circulation dispersion for 10 minutes, placing the mixture in a three-necked flask, and then placing the three-necked flask in a water bath at 70°C-90°C, stirring and dispersing at a stirring speed of 100-150 r / min for 30 minutes, and then cooling to 20°C to obtain a silica dispersion with double bonds and amine groups on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11);

[0015] S13) preparing a first polymer template emulsion, the specific steps are as follows:

[0016] S13-1) mixing butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt % ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and a reactive emulsifier in weight proportions of 0.1-20:0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08 to prepare a first mixed solution;

[0017] S13-2) By means of starvation polymerization, 0.5 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water and 0.005 to 1 part by weight of an initiator are added dropwise to 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt% at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion having a cross-linked core-shell structure;

[0018] S14) preparing a second polymer template emulsion, the specific steps are as follows:

[0019] S14-1) mixing butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier in a weight ratio of 0.1-6:0.1-6:0.1-6:0.01-0.02 to prepare a second mixed solution;

[0020] S14-2) by means of starvation polymerization, at a temperature of 60 to 65° C., 0.3 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silica dispersion having double bonds and amine groups on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 242 parts by weight of a first polymer template latex at a constant speed, after the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material inlaid with silica particles having a particle size of 20 nm to 30 nm is coated on the surface of the polyacrylamide latex particles, to obtain a second polymer template latex having a bayberry-like multilayer core-shell structure;

[0021] S15) preparing a third polymer template emulsion, the specific steps are as follows:

[0022] S15-1) mixing ammonium polyphosphate, ethanol and deionized water in a weight ratio of 5-15:0.5-1:2-10 to prepare a third mixed solution;

[0023] S15-2) by means of ion exchange reaction, at a temperature of 30 to 40° C., 7 to 26 parts by weight of the third mixed solution are added dropwise to 51 to 326 parts by weight of the second polymer template emulsion at a constant speed, stirred at a stirring speed lower than 80 r / min, and refluxed and condensed for 4 hours under this temperature condition to obtain a third polymer template emulsion with a multilayer core-shell structure having linear ammonium polyphosphate as the outermost branch chain;

[0024] S16) preparing organic / inorganic composite latex particles, the specific steps are as follows:

[0025] S16-1) preparing a fourth mixed solution by mixing glycidyl methacrylate, an initiator and deionized water in a ratio of 5 to 15: 0.01 to 0.2: 5 to 10 parts by weight;

[0026] S16-2) Add 10 to 25 parts by weight of the fourth mixed solution to 58 to 352 parts by weight of the third polymer template latex at a constant speed under a temperature condition of 60 to 65°C, stir at a stirring speed lower than 80 r / min, and reflux condense for 3 hours under this temperature condition to form a second polymer with linear poly(methyl methacrylate) glycidyl as a branch on the surface of the latex particles, and obtain organic / inorganic composite latex particles with a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking, that is, obtain polyacrylamide-based organic / inorganic hybrid nanomaterials.

[0027] A fire-proof pre-reaction liquid comprises at least the following components: 68 to 377 parts by weight of polyacrylamide-based organic / inorganic hybrid nanomaterials, 0.5 to 4 parts by weight of cellulose solvents, 0.5 to 2.5 parts by weight of catalysts and 10 to 30 parts by weight of deionized water; wherein the polyacrylamide-based organic / inorganic hybrid nanomaterials are the above-mentioned polyacrylamide-based organic / inorganic hybrid nanomaterials.

[0028] The above-mentioned fire-proof pre-reaction liquid also includes 1 to 5 parts by weight of a carbonizing agent, 0.001 to 0.05 parts by weight of a defoaming agent and 0.1 to 1 parts by weight of a rheological aid; the carbonizing agent is compounded from one or more of sucrose, fructose, glucose and maltose with pentaerythritol, wherein the proportion of pentaerythritol in the carbonizing agent is greater than or equal to 25wt%; the rheological aid is one or more of hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose; the cellulose solvent is one or more of dipropylene glycol methyl ether and N-methyl morpholine oxide; the catalyst is compounded from a hydrochloric acid solution with a mass percentage less than or equal to 20% and one or two of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite, wherein the hydrochloric acid solution accounts for less than or equal to 90wt% of the catalyst; the defoaming agent is one or two of a polysiloxane defoaming agent and a polyether defoaming agent.

[0029] The method for preparing the fire-proof pre-reaction liquid comprises the following steps:

[0030] S21), mixing a carbonizing agent, a rheological additive, and deionized water in a weight ratio of 1-5:0.1-1:10-25, stirring at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and aging for 12 hours to obtain a transparent and dynamically reversible gel material;

[0031] S22) polyacrylamide-based organic / inorganic hybrid nanomaterials and cellulose solvents are mixed in a weight ratio of 68-377:0.5-4, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to form a uniform suspension; 11-30 parts by weight of gelling material are added thereto, and stirred at a stirring speed of less than 80 r / min for 80 minutes at room temperature to obtain a pre-reaction liquid; 0.5-2.5 parts by weight of a catalyst and 0.001-0.05 parts by weight of a defoaming agent are added to the pre-reaction liquid in sequence, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to obtain a fire-retardant pre-reaction liquid, which is left to stand for use.

[0032] The above-mentioned fire-retardant pre-reaction liquid is used for flame retardant treatment of transparent cellulose modified soda-lime glass products and forming a fire-retardant layer with a thickness of 0.02 to 0.3 mm on the surface of the glass products. The specific operation is: spray the fire-retardant pre-reaction liquid onto the surface of the transparent cellulose modified soda-lime glass product, let it stand for 50 minutes, and after the surface of the glass is dry, put it into a 50°C oven for baking for 4 hours, and then heat it to 80°C and bake for 3 hours, so that the cellulose on the glass surface and the fire-retardant pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure.

[0033] By means of the above technical solution, the fireproof layer material and the preparation method thereof and the fireproof glass provided by the present invention have at least the following advantages:

[0034] 1. By introducing double bonds (alkenyl silane coupling agent) and amine groups (amino silane coupling agent) on the hydrophilic silica surface, reaction sites are provided for grafting the two outermost linear polymers (ammonium polyphosphate and poly(glycidyl methacrylate)) onto the core-shell polymer surface: the amine groups in the functional shell polymer can graft ammonium polyphosphate onto the functional shell surface through an ion exchange reaction in an ethanol solution to obtain linear grafted ammonium polyphosphate; at the same time, the alkenyl groups in the functional shell can undergo polymerization reaction with glycidyl methacrylate to form a linear poly(glycidyl methacrylate) polymer, which provides a precursor for the subsequent ring-opening and curing of epoxy groups with ionic reaction activity, thereby forming a material with a multiple network structure; the use of cellulose-based substances as rheological additives in the fire-retardant pre-reaction liquid can improve the leveling of the system during brushing, and can also penetrate into multiple cross-linked networks to form physical cross-links, thereby further entangled with the cellulose on the surface of transparent cellulose-modified soda-lime glass for construction, thereby improving the cross-linking degree of the coating.

[0035] 2. The introduction of polyacrylamide in the flexible core layer, silica particles in the functional shell layer, and cross-linking agent divinyl sulfone ensures the toughness, impact strength, hardness and environmental adaptability of the coating: Since glass windows are subject to wiping, wind deformation and weather resistance during use, the silica particles in the polymer functional shell layer further improve the toughness and impact strength of the system on the basis of the original multiple cross-linking. At the same time, the introduction of the multiple cross-linking system also provides conditions for improving the weather resistance of organic coatings for glass windows.

[0036] 3. By using soap-free emulsification technology to gradually polymerize, the amount of emulsifier is further optimized by introducing reactive emulsifiers; at the same time, compared with the blended fire-retardant pre-reaction liquid, the hydrophilic groups in the monomer are effectively distributed in each layer of the latex particles by using the particle design principle, which reduces the number of hydrophilic groups concentrated and distributed in the outermost layer, thereby reducing the viscosity of the solution, making it easier to penetrate the inside of the transparent lignin layer on the glass surface, and improving the flame retardancy of the product; by using ion exchange method and low-temperature polycondensation method, ammonium polyphosphate and melamine formaldehyde are grafted to the surface and surface of latex particles respectively at a temperature below 50°C. In the reinforcing transition layer, the cross-linked network structure is avoided from being formed in the pre-reaction liquid in advance. At the same time, after being coated on the glass surface in the later stage, the gradient heating method is used to produce a synergistic effect between the components in the fire-retardant pre-reaction liquid, thereby ensuring the realization of the functions of the multiple cross-linking system. A high-performance flame-retardant fire-resistant glass material is prepared, which can be used in a low-temperature environment of -25°C±1°C, has a coating that is resistant to ultraviolet radiation for more than 2000 hours, and a flame retardant grade that meets the B1 low flammability material standard specified in DIN4102 (German standard) and the UL94-V0 high flame retardant material standard (American Insurance Association standard).

[0037] 4. The fireproof layer formed after the fireproof pre-reaction liquid of the present invention is cured has the characteristics of resistance to low temperature, resistance to ultraviolet radiation, resistance to impact, high hardness and resistance to water washing. The reason is that the specially designed multi-layer core-shell structure and preparation process optimize the effective cross-linking of the particles themselves and between the particles, reduce the swelling degree of the multi-layer core-shell latex particles and the film layer, such as the solvent in the system and the moisture in the use environment, further improve the density of the particles in the film forming process, and reduce the moisture content in the film layer on the basis of improving the strength of the film polymer. Correspondingly, the destruction of the internal structure of the film layer by ice crystals at low temperatures is avoided; the multiple cross-linking system also increases the ultraviolet radiation resistance of the film layer; at the same time, silica particles with double bonds and amine groups are polymerized in the functional shell layer. The particles are uniformly distributed in the shape of a "sea roxburghii" linear ammonium polyphosphate and polymethacrylic acid molecular chains on the outer surface of the latex particles. At the same time, with the help of the high hardness of the silica inorganic particles, the advantage of the "soft core and hard shell" of the latex particles is achieved. The soft core can ensure that the coating has excellent impact resistance, and the organic\inorganic composite hard shell with a cross-linked structure gives the coating scratch resistance and improves the coating's resistance to ultraviolet radiation. The "sea roxburghii" structure increases the entanglement of the film layer with the transparent cellulose on the glass surface, and the multiple network cross-linked structures firmly fix these entanglements together, thereby improving the adhesion of the coating. At the same time, this "sea roxburghii" structure can give the coating a "lotus effect", further improving the coating's resistance to water washing.

[0038] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a schematic diagram of the structure of the polyacrylamide-based organic / inorganic composite latex particles of the present invention.

[0040] In the figure, 1-flexible core layer; 2-reinforced transition layer; 3-functional shell layer; 4-hydrophilic silica nanoparticles; 5-linear ammonium polyphosphate; 6-linear poly(glycidyl methacrylate). DETAILED DESCRIPTION

[0041] The polyacrylamide-based organic / inorganic hybrid nanomaterial of the present invention is composed of polyacrylamide-based organic / inorganic composite latex particles, which are composited by at least two fireproof substrates, the two fireproof substrates are functional shell layer and flexible core layer, respectively, and a reinforcing transition layer is arranged between adjacent substrates, at least one of the reinforcing transition layers is a polymer layer containing melamine formaldehyde material with a cross-linked network structure. Figure 1As shown, the functional shell is a polymer layer in which surface-modified hydrophilic silica nanoparticles are embedded and contains phosphorus-containing polymers and silicon-containing polymers, and at least one of the polymers in the functional shell is a polymer that can form an interpenetrating network structure with cellulose, and in the functional shell, one end of linear ammonium polyphosphate and one end of linear poly(glycidyl methacrylate) are respectively grafted on the surface-modified hydrophilic silica nanoparticles, and the other end of linear ammonium polyphosphate and the other end of linear poly(glycidyl methacrylate) are respectively located outside the shell of the functional shell. Since the silica particles with double bonds and amine groups on the surface have obvious hydrophilicity, when preparing the functional shell of polyacrylamide-based organic / inorganic composite latex particles, in the functional shell shell formed with lipophilic monomers, the silica particles, as a reinforcing phase, tend to be enriched on the shell surface, which will expose the double bonds and amine groups on the shell surface, making it easy for the double bonds to polymerize with glycidyl methacrylate to form linear poly(glycidyl methacrylate) polymers, and for the amine groups to react with ammonium polyphosphate to form ammonium polyphosphate polymers. The polyacrylamide-based organic / inorganic composite latex particles are polyacrylamide-based organic / inorganic composite latex particles with a "roxburghii"-shaped multi-layer core-shell structure and multiple cross-linking. The fire-proof pre-reaction liquid is composed of the following substances in parts by weight: 2 to 3 parts of tetraethyl orthosilicate, 0.02 to 0.04 parts of concentrated ammonia water with a concentration of 25wt%, 36 to 94 parts of deionized water, 0.1 to 0.5 parts of alkenyl silane coupling agent, 0.1 to 0.5 parts of amino silane coupling agent, 0.501 to 1.02 parts of ethanol, 20 to 150 parts of polyacrylamide solution, 0.2 to 26 parts of butyl acrylate, and 0.5 to 26 parts of methyl methacrylate. 6-7 parts, melamine 0.1-20 parts, styrene 0.1-20 parts, divinyl sulfone 0.01-0.03 parts, 20wt% ammonia water 0.05-0.2 parts, 2,4-methyl-3-cyclohexene carboxaldehyde 0.1-20 parts, methacrylic acid 0.1-6 parts, ammonium polyphosphate 5-15 parts, glycidyl methacrylate 5-15 parts, emulsifier 0.012-0.1 parts, initiator 0.018-1.23 parts, carbon former 1-5 parts, rheological additive 0.1-1 parts, cellulose solvent 0.5-4, catalyst 0.5-2.5 parts, defoamer 0.001-0.05 parts.The polyacrylamide-based organic / inorganic composite latex particles are single-peak, narrowly distributed particles; the polyacrylamide-based organic / inorganic composite latex particles are narrowly distributed particles prepared by means of a soap-free emulsion polymerization method and a particle design principle, wherein the flexible core layer material is polyacrylamide particles and aggregates thereof, and the functional shell layer materials are respectively a reinforcing transition layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) containing a melamine formaldehyde material with a cross-linked network structure, a functional shell layer of a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silicon dioxide particles with a particle size of 20nm to 30nm, and an outermost roxburghii-shaped structure composed of linear ammonium polyphosphate and linear poly(glycidyl methacrylate), and the pH value of the fire-retardant pre-reaction liquid is between 5 and 8.

[0042] As a preferred embodiment, the fire-proof pre-reaction liquid is composed of the following raw materials, in parts by weight: 2.1 to 2.7 parts of tetraethyl orthosilicate, 0.025 to 0.035 parts of concentrated ammonia water with a concentration of 25wt%, 45 to 80 parts of deionized water, 0.2 to 0.4 parts of alkenyl silane coupling agent, 0.2 to 0.4 parts of amino silane coupling agent, 0.6 to 0.9 parts of ethanol, 30 to 120 parts of polyacrylamide solution, 0.5 to 20 parts of butyl acrylate, 1.5 to 5.5 parts of methyl methacrylate, 0.5 to 15 parts of melamine, and 0.5 to 15 parts of styrene. parts, divinyl sulfone 0.015-0.025 parts, 20wt% ammonia water 0.07-0.15 parts, 2,4-methyl-3-cyclohexene carboxaldehyde 0.5-15 parts, methacrylic acid 0.5-5 parts, ammonium polyphosphate 7.5-12 parts, glycidyl methacrylate 7.5-12 parts, emulsifier 0.02-0.08 parts, initiator 0.03-1 parts, carbon former 1.5-3.5 parts, rheological additive 0.2-0.8 parts, cellulose solvent 1-3.5, catalyst 0.8-2 parts, defoamer 0.005-0.04 parts.

[0043] As a preferred embodiment, the solid content of the polyacrylamide emulsion is 35wt% to 45wt%, the degree of polymerization of the polyacrylamide particles is 15000 to 25000, the particle size is 50nm to 80nm, the particle size distribution is a single peak narrow distribution, and the thickness of the reinforcing transition layer, the thickness of the functional shell layer and the thickness of the graft on the surface of the functional shell layer of the polyacrylamide-based organic / inorganic composite latex particles prepared based on the polyacrylamide particles are 35nm to 45nm, 25nm to 35nm, and 40nm to 120nm, respectively.

[0044] The invention uses polyacrylamide-based organic / inorganic composite latex particles as the main raw material of the fireproof pre-reaction liquid. The polyacrylamide particle size in the polyacrylamide emulsion is 40nm-200nm, the solid content is 15wt%-55wt%, the flexible core layer particle size of the polyacrylamide-based organic / inorganic composite latex particles is 40nm-200nm, and the particle size distribution is a single peak narrow distribution; the reinforcing transition layer of the polyacrylamide-based organic / inorganic composite latex particles is a material of poly(butyl acrylate-containing melamine formaldehyde material) with a cross-linked network structure. Styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer, the thickness of the reinforcing transition layer is 35nm~45nm; the functional shell layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with 20nm~30nm silica particles, the thickness of the functional shell layer is 25nm~35nm; the surface graft of the functional shell layer composed of linear ammonium polyphosphate and linear poly(glycidyl methacrylate) (similar to the thorns on the "thorn pear"), the thickness is 40nm~120nm. Polyacrylamide-based organic / inorganic composite latex particles are narrowly distributed particles. The present invention has the characteristics of multiple cross-linking system, low viscosity of pre-reaction liquid, good impact resistance of the coating, water washing resistance and good weather resistance. At the same time, the low-temperature use temperature can reach -25°C±1°C, the coating is resistant to ultraviolet radiation for more than 2000 hours, and the flame retardant grade meets the B1 low flammability material standard specified in DIN4102 (German standard) and the UL94-V0 high flame retardant material standard (American Insurance Association standard).

[0045] The reason why the polyacrylamide-based organic / inorganic composite latex particles are resistant to low temperature, ultraviolet radiation, impact and water washing is:

[0046] 1. The specially designed multi-layer core-shell structure and preparation process optimize the effective cross-linking between particles, reduce the swelling degree of the multi-layer core-shell latex particles and the film layer caused by the solvent in the system and the moisture in the use environment, further improve the density of the particles in the film forming process, and reduce the moisture content in the film layer on the basis of improving the strength of the film polymer. Accordingly, it avoids the destruction of the internal structure of the film layer by ice crystals at low temperatures;

[0047] 2. The multiple cross-linking system also increases the film's resistance to ultraviolet radiation;

[0048] 3. Silica particles with double bonds and amine groups are polymerized in the functional shell layer to achieve uniform distribution of "thorn pear"-shaped linear ammonium polyphosphate and polymethacrylic acid molecular chains on the outer surface of the latex particles. With the high hardness of silica inorganic particles, the advantages of "soft core and hard shell" of latex particles are achieved. The soft core can ensure that the coating has excellent impact resistance, and the cross-linked organic\inorganic composite hard shell gives the coating scratch resistance and improves the coating's resistance to ultraviolet radiation;

[0049] 4. The "sea buckthorn"-like structure increases the entanglement between the film layer and the cellulose on the glass surface. At the same time, the multiple network cross-linked structures firmly fix these entanglements together, improving the adhesion of the coating. At the same time, this "sea buckthorn"-like structure can give the coating a "lotus effect", further improving the coating's resistance to water washing.

[0050] The fireproof pre-reaction liquid of the present invention exists in the form of a dispersion liquid, and the mass concentration of the dispersion liquid is 40%-60%.

[0051] As a preferred embodiment, the emulsifier is at least one of reactive emulsifiers (such as nonylphenol allyl polyoxyethylene ether ammonium sulfate, allyloxydecyl polyoxyethylene ether ammonium sulfate, etc.); the initiator is at least one of thermal initiators (such as dibenzoyl peroxide, azobisisobutyronitrile, etc.) and redox initiators (such as ammonium persulfate and sodium bisulfite, etc.); the alkenyl silane coupling agent is at least one of vinyl triperoxide tert-butyl silane, vinyl triethoxysilane, butadienyl triethoxysilane, vinyl trimethoxysilane, isobutylenyl triethoxysilane, and vinyl tri(β-methoxyethoxy) silane; the amino silane coupling agent is at least one of one or more silanes selected from phenylaminomethyl triethoxysilane, γ-aminopropyl trimethoxysilane, N-β (aminoethyl)-γ-aminopropyl triethoxysilane, and 3-aminopropyl triethoxysilane; the carbon-forming agent is sucrose, fructose, glucose, or the like. The invention relates to a material comprising at least one of glucose and maltose compounded with pentaerythritol; the rheological additive is at least one of hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose; the cellulose solvent is at least one of dipropylene glycol methyl ether and N-methyl morpholine oxide solution; the pigment is at least one of organic pigment and inorganic pigment; the pigment auxiliary agent is at least one of N-methyl pyrrolidone, N-ethyl pyrrolidone, Nd butyl pyrrolidone and N-octyl pyrrolidone; the catalyst is at least one of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite compounded with dilute hydrochloric acid solution (≤20wt%); the defoamer is at least one of polysiloxane defoamers (such as BYK024 and BYK088) and polyether defoamers (such as GP type glycerol polyether, GPE type polyoxyethylene (polyoxypropylene) ether and PPG type polypropylene glycol).

[0052] The functions of the raw materials used in the fire-proof pre-reaction liquid of the present invention are as follows:

[0053] Polyacrylamide-based organic / inorganic composite latex particles are mixed with a solvent to form a fire-retardant pre-reaction liquid of polyacrylamide-based organic / inorganic composite latex particles having a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking. After the fire-retardant pre-reaction liquid comes into contact with transparent cellulose-modified soda-lime glass, it can penetrate into the multiple cross-linking network to form physical cross-linking, thereby further entangled with the cellulose on the glass surface and improving the cross-linking degree of the coating; at the same time, this "sea buckthorn"-shaped structure can give the coating a "lotus effect", further improving the coating's resistance to water washing.

[0054] The multilayer core-shell structure polyacrylamide-based organic / inorganic composite latex particles used in the embodiment of the present invention are core-shell structures, which means that two or more monomers are polymerized in stages or multiple stages under certain conditions, so that different components are enriched on the inside or outside of the particles, i.e., core-shell particles, thereby giving different functions to the core and the shell, and obtaining particles with excellent performance; wherein the flexible core layer material is polyacrylamide particles and their aggregates, the reinforcing transition layer material is a poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer containing melamine formaldehyde material having a cross-linked network structure, the functional shell layer material is a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm, and the surface graft of the functional shell layer is linear ammonium polyphosphate and linear poly(glycidyl methacrylate), the physical morphology of the polyacrylamide-based organic / inorganic composite latex particles is similar to that of roxburghii, and this characteristic The specially designed multi-layer core-shell structure and preparation process optimize the effective cross-linking between particles themselves and particles, reduce the swelling degree of multi-layer core-shell latex particles and film layers such as solvents in the system and moisture in the use environment, further improve the density of particles in the film forming process, and reduce the moisture content in the film layer on the basis of improving the strength of the film polymer. Correspondingly, the damage of the internal structure of the film layer by ice crystals at low temperatures is avoided; the multiple cross-linking system also increases the ultraviolet radiation resistance of the film layer; at the same time, silica particles with double bonds and amine groups are polymerized in the functional shell layer to achieve the uniform distribution of "sea buckthorn"-shaped linear ammonium polyphosphate and polymethacrylic acid molecular chains on the outer surface of the latex particles. With the help of the high hardness of silica inorganic particles, the advantage of "soft core and hard shell" of latex particles is achieved. The soft core can ensure that the coating has excellent impact resistance, and the organic\inorganic composite hard shell with a cross-linked structure gives the coating scratch resistance, and can also improve the coating hardness and ultraviolet radiation resistance.

[0055] The above-mentioned polyacrylamide-based organic / inorganic composite latex particles are narrowly distributed nanoparticles with a particle size of 140nm-400nm. The study found that: by relying on the principle of "particle design", the fire-retardant pre-reaction liquid composed of low-viscosity polyacrylamide-based organic / inorganic composite latex particles with multi-layer core-shell structure has a shear-thinning property because the entanglement between the outermost layer of branched polymers is only physical entanglement. Through the optimization of other additives, the addition of other additives does not affect the shear-thinning property of the system. Therefore, the finished fire-retardant pre-reaction liquid also has a shear-thinning property.

[0056] Since the polyacrylamide-based organic / inorganic composite latex particles are narrowly distributed nanoparticles, they have multiple cross-linking systems, low pre-reaction liquid viscosity, good coating impact resistance, and water washing resistance. At the same time, the low-temperature use temperature can reach -25℃±1℃, the coating is resistant to ultraviolet radiation for more than 2000 hours, and the flame retardant grade meets the B1 low flammability material standard specified in DIN4102 (German standard) and UL94-V0 high flame retardant material standard (American Insurance Association standard).

[0057] The polyacrylamide-based organic / inorganic composite latex particles provide reaction sites for grafting the two outermost linear polymers (ammonium polyphosphate and poly(glycidyl methacrylate)) onto the surface of the core-shell polymer by introducing double bonds (alkenyl silane coupling agent) and amine groups (amino silane coupling agent) onto the surface of the hydrophilic silica: the amine groups in the functional shell polymer can graft ammonium polyphosphate onto the functional shell surface through an ion exchange reaction in an ethanol solution to obtain linear grafted ammonium polyphosphate; at the same time, the alkenyl groups in the functional shell can undergo polymerization reaction with glycidyl methacrylate to form a linear poly(glycidyl methacrylate) polymer, which provides a precursor for the subsequent ring-opening and curing of the epoxy groups with ionic reaction activity, thereby forming a material with a multiple network structure; the use of cellulose-based substances as rheological additives in the fire-retardant pre-reaction liquid can improve the leveling of the system when it is applied, and can also penetrate into the multiple cross-linked networks to form physical cross-links, thereby further entangled with the cellulose on the surface of the transparent cellulose-modified soda-lime glass for construction, thereby improving the cross-linking degree of the coating.

[0058] It should be emphasized that in the polyacrylamide-based organic / inorganic hybrid nanomaterial of the present invention, the nano-polyacrylamide-based organic / inorganic composite latex particles themselves have the properties of resistance to low temperature, resistance to ultraviolet radiation, resistance to impact, and resistance to water washing.

[0059] The polyacrylamide-based organic / inorganic hybrid material of the present invention is prepared by the following steps:

[0060] S11) mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3:0.02-0.04:8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm-30 nm;

[0061] S12) putting the silica seed solution, alkenyl silane coupling agent, amino silane coupling agent and ethanol into a high-pressure homogenizer for circulation dispersion for 10 minutes according to 10-25: 0.1-0.5: 0.1-0.5: 0.001-0.02, and then putting it into a three-necked flask, and then putting the three-necked flask into a water bath at 70° C. to 90° C., stirring and dispersing at a stirring speed of 100-150 r / min for 30 minutes, and then cooling to 20° C. to obtain a silica dispersion with double bonds and amine groups on the surface;

[0062] S13) mixing butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt % ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and reactive emulsifier in weight parts of 0.1-20:0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08 to prepare a first mixed solution; using a starvation polymerization method, at a temperature of 60-65° C., at a constant speed, adding 0.5-80 wt % of butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt % ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and reactive emulsifier in weight parts of 0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08 to prepare a first mixed solution; The first mixed solution, 6 to 12 parts by weight of deionized water and 0.005 to 1 part by weight of an initiator are added dropwise to 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt%. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion having a cross-linked core-shell structure;

[0063] S14) mixing butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier in a weight ratio of 0.1-6:0.1-6:0.1-6:0.01-0.02 to prepare a second mixed solution; using a starvation polymerization method, at a temperature of 60-65° C., 0.3-18 weight parts of the second mixed solution, 15-40 weight parts of deionized water, 10-26 weight parts of a silica dispersion with double bonds and amine groups on the surface, and 0.003-0.03 weight parts of an initiator are dropwise added to 26-242 weight parts of a first polymer template emulsion at a constant speed; after the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material embedded with silica particles with a particle size of 20 nm to 30 nm is coated on the surface of the polyacrylamide latex particles, thereby obtaining a second polymer template emulsion having a bayberry-like multilayer core-shell structure;

[0064] S15) ammonium polyphosphate, ethanol and deionized water are mixed in a weight ratio of 5 to 15:0.5 to 1:2 to 10 to obtain a third mixed solution; by means of an ion exchange reaction, 7 to 26 weight parts of the third mixed solution are added dropwise to 51 to 326 weight parts of the second polymer template emulsion at a constant speed at a temperature of 30 to 40° C., stirred at a stirring speed lower than 80 r / min, and refluxed and condensed at this temperature for 4 hours to obtain a third polymer template emulsion with a multilayer core-shell structure having linear ammonium polyphosphate as the outermost branch chain;

[0065] S16) preparing a fourth mixed solution in the weight proportion of 5-15:0.01-0.2:5-10 of glycidyl methacrylate, initiator and deionized water; dropping 10-25 weight parts of the fourth mixed solution into 58-352 weight parts of the third polymer template latex at a constant speed under a temperature condition of 60-65°C, stirring at a stirring speed lower than 80r / min, and reacting under reflux condensation at this temperature condition for 3h to form a second polymer with linear polymethacrylate glycidyl methacrylate as a branch on the surface of the latex particles, thereby obtaining polyacrylamide-based organic / inorganic composite latex particles having a "sea buckthorn"-shaped multi-layer core-shell structure and being multiply cross-linkable.

[0066] S17) mixing a carbonizing agent, a rheological additive, and deionized water in a weight ratio of 1 to 5:0.1 to 1:10 to 25, stirring at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and aging for 12 hours to obtain a transparent and dynamically reversible gel material;

[0067] S18) Mixing polyacrylamide-based organic / inorganic composite latex particles having a "sea roxburghii"-shaped multilayer core-shell structure and multiply cross-linkable, and cellulose solvent in a weight ratio of 68-377:0.5-4, stirring at a stirring speed of less than 80 r / min for 40 minutes at room temperature to form a uniform suspension; then adding 11-30 parts by weight of a transparent, dynamically reversible gelling material thereto, stirring at a stirring speed of less than 80 r / min for 80 minutes at room temperature to obtain a pre-reaction liquid; then adding 0.5-2.5 parts by weight of a catalyst and 0.001-0.05 parts by weight of a defoaming agent to the pre-reaction liquid in sequence, stirring at a stirring speed of less than 80 r / min for 40 minutes at room temperature to obtain a fire-proof pre-reaction liquid, and standing for use;

[0068] S19) According to the standard requirements of XF 159-2011 "Water-based flame retardants", the fire-retardant pre-reaction liquid is sprayed onto the surface of the transparent cellulose-modified soda-lime glass product, and allowed to stand for 50 minutes. After the surface of the glass product is dry, it is placed in a 50°C oven and baked for 4 hours, and then the temperature is raised to 80°C and baked for 3 hours, so that the cellulose on the glass surface and the fire-retardant pre-reaction liquid covering it form a multi-crosslinking system to form an interpenetrating network structure, thereby improving the flame retardant properties of the product.

[0069] Furthermore, in the above steps, the polyacrylamide particle size in the polyacrylamide emulsion is 40nm-200nm, the solid content is 15wt%-55wt%, the flexible core layer particle size of the polyacrylamide-based organic / inorganic composite latex particles prepared based on the polyacrylamide particles is 40nm-200nm, and the particle size distribution is a single peak narrow distribution; in the polyacrylamide-based organic / inorganic composite latex particles, the reinforcing transition layer materials are respectively poly(butyl acrylate-styrene) containing melamine formaldehyde material with a cross-linked network structure - divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer, the thickness of the reinforcing transition layer is 35nm to 45nm; the functional shell polymer is a poly (butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm, the thickness of the functional shell is 25nm to 35nm; and the functional shell surface graft is linear ammonium polyphosphate and linear polymethacrylate glycidyl, the thickness of the functional shell surface graft is 40nm to 120nm. The polyacrylamide-based organic / inorganic composite latex particles are narrowly distributed particles.

[0070] Furthermore, in the above step S16), the stirring time is 20 to 60 minutes, preferably 40 minutes.

[0071] When preparing the fireproof pre-reaction liquid in the embodiment of the present invention, firstly, tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25wt%, and deionized water are mixed, and the mixture is allowed to stand for aging to obtain a silicon dioxide seed solution; the silicon dioxide seed solution, alkenyl silane coupling agent, amino silane coupling agent, and ethanol are homogenized and dispersed under high pressure, and the stirring reaction is continued at a stirring speed of less than 150r / min to obtain a silicon dioxide dispersion liquid with double bonds and amino groups on the surface; butyl acrylate, melamine, styrene, divinyl sulfone, ammonia water with a concentration of 20wt%, 2,4-methyl-3-cyclohexene formaldehyde, and a reactive emulsifier are mixed to obtain a first mixed solution; and the mixture is subjected to starvation polymerization to obtain a silicon dioxide dispersion liquid having double bonds and amino groups on the surface. The method comprises the following steps: dropping a first mixed solution, deionized water, and an initiator into a polyacrylamide emulsion to obtain a first polymer template emulsion with a core-shell structure; mixing butyl acrylate, methyl methacrylate, methacrylic acid, and an emulsifier to obtain a second mixed solution; using a starvation polymerization method, dropping the second mixed solution, deionized water, a silica dispersion with double bonds and amine groups on the surface, and an initiator into the first polymer template emulsion to obtain a second polymer template emulsion with a bayberry-like multilayer core-shell structure; mixing ammonium polyphosphate, ethanol, and deionized water to obtain a third mixed solution; dropping the third mixed solution into the second polymer template emulsion using an ion exchange reaction; The template emulsion is subjected to reflux condensation reaction to obtain a third polymer template emulsion with a multi-layer core-shell structure having linear ammonium polyphosphate as the outermost branch chain; glycidyl methacrylate, an initiator and deionized water are mixed to obtain a fourth mixed solution; the fourth mixed solution is added dropwise to the third polymer template emulsion, refluxed condensation reaction is performed to obtain polyacrylamide-based organic / inorganic composite latex particles having a "sea roxburghii"-shaped multi-layer core-shell structure and capable of multiple crosslinking; a carbonizing agent, a rheological additive and deionized water are mixed, stirred at a stirring speed of less than 100 r / min, and allowed to stand for aging to obtain a gel material; the "sea roxburghii"-shaped multi-layer core-shell structure and capable of multiple crosslinking are added dropwise to the fourth mixed solution; the ... "sea roxburghii"-shaped multi-layer core-shell structure and capable of multiple crosslinking are obtained. The cross-linked polyacrylamide-based organic / inorganic composite latex particles and cellulose solvent are mixed and stirred at a stirring speed lower than 80 r / min, and then the gelling material is added thereto and stirred at a stirring speed lower than 80 r / min to obtain a pre-reaction liquid; the catalyst and the defoaming agent are added to the pre-reaction liquid in sequence and stirred at a stirring speed lower than 80 r / min to obtain a fire-proof pre-reaction liquid, and the fire-proof pre-reaction liquid is sprayed onto the surface of a transparent cellulose-modified soda-lime glass product, and the glass surface is baked after being dried, so that the cellulose on the glass surface and the fire-proof pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure, thereby improving the flame retardant properties of the product.

[0072] The fireproof material formed after the fireproof pre-reaction liquid provided by the embodiment of the present invention reacts is an intumescent flame retardant system. When encountering a fire, the ammonium polyphosphate on the surface of the glass cellulose is thermally decomposed to generate phosphoric acid and pyrophosphoric acid with strong dehydration effect, so that the carbon forming agent is esterified, and then dehydrated and carbonized. The water vapor formed by the reaction and the ammonia decomposed in the melamine formaldehyde resin can also expand the carbon layer, and finally form a multi-porous carbon layer, thereby isolating air and heat conduction, protecting glass products, and achieving the purpose of flame retardancy. At the same time, the fireproof material formed after the fireproof pre-reaction liquid provided by the embodiment of the present invention reacts has the following advantages: good thermal stability, and the multiple cross-linking system ensures that the coating can withstand high temperature reprocessing above 150°C after low-temperature baking; when a fire suddenly occurs, a large amount of volatile substances can be released, blocking oxygen, and expanding and foaming at the same time; this "thorn pear"-shaped multi-layer core-shell structure and multi-crosslinkable fireproof structure can be evenly distributed on the surface of the wood fiber during the film forming process, and can form a layer of expanded carbon that completely covers the surface of the material in the fire to prevent it from dripping and spreading the fire.

[0073] As a preferred embodiment, the thickness of the fireproof material formed after the fireproof pre-reaction liquid reacts is 0.02 to 0.3 mm.

[0074] The present invention can control the thickness of the fireproof material formed after the fireproof pre-reaction liquid reacts to 0.02-0.3 mm, and manufacture a thinner fireproof layer under the premise of ensuring fireproof performance, reduce the production cost of the window, and expand the application scope of the fireproof material. The fireproof material formed after the fireproof pre-reaction liquid of the embodiment of the present invention reacts will expand to form a porous heat-insulating layer after encountering fire, and the thickness of the expansion layer is about 15-20 times the thickness of the original fireproof layer, and gradually forms a heat-insulating layer of about 1mm-4mm; if the thickness of the fireproof material is less than 0.02mm, the fireproof layer is too thin, and the formed heat-insulating layer cannot isolate the heat transfer within a certain period of time, resulting in the overall fireproof time being lower than the design value; if the thickness of the fireproof material is greater than 0.3mm, the fireproof layer is too thick, which will cause the excess fireproof pre-reaction liquid on the glass surface to be unable to continue to form an effective network entanglement with cellulose, and also block the volatilization of the solution inside the coating, which greatly increases the early baking time, the cost is too high, and the fireproof performance is reduced.

[0075] The present invention is further described below with reference to specific embodiments, but is not intended to limit the present invention.

[0076] The reagents used in the embodiments of the present invention are all commercially available products.

[0077] Example 1

[0078] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0079] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0080] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of ammonia water with a concentration of 20wt%, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent. Since the particle size of the polyacrylamide particles in the polyacrylamide emulsion is narrowly distributed, the particle size of the multilayer core-shell structure latex particles is also unimodal, similarly, the particle size of the flexible core layer particles and the multilayer core-shell structure latex particles in the following embodiments is also narrowly distributed;

[0081] (2) Prepare a fire-proof pre-reaction liquid by the following steps:

[0082] 2.3 kg of tetraethyl orthosilicate, 0.03 kg of concentrated ammonia water with a concentration of 25 wt%, and 15 kg of deionized water were mixed and allowed to stand for 36 hours to generate a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, and the particle size of the silicon dioxide particles was 20 nm to 30 nm;

[0083] Put 12.5kg of silica seed solution, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent and 0.01kg of ethanol into a high-pressure homogenizer for circulation dispersion for 10 minutes, put them into a three-necked flask, put the three-necked flask into a water bath at 70℃~90℃, stir and disperse at a stirring speed of 100~150r / min for 30 minutes, and then cool to 20℃ to obtain a silica dispersion with double bonds and amine groups on the surface;

[0084] 5 kg of butyl acrylate, 3 kg of melamine, 3 kg of styrene, 0.02 kg of divinyl sulfone, 0.1 kg of 20 wt% ammonia water, 4 kg of 2,4-methyl-3-cyclohexene carboxaldehyde, and 0.04 kg of emulsifier are mixed to prepare a first mixed solution; by means of a starvation polymerization method, 15.16 kg of the first mixed solution, 7.5 kg of deionized water, and 0.05 kg of an initiator are added dropwise to 40 kg of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt% at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion having a cross-linked core-shell structure;

[0085] 2kg of butyl acrylate, 2kg of methyl methacrylate, 2kg of methacrylic acid, and 0.015kg of an emulsifier are used to prepare a second mixed solution; 6.015kg of the second mixed solution, 20kg of deionized water, 13.11kg of a silicon dioxide dispersion with double bonds and amine groups on the surface, and 0.02kg of an initiator are added dropwise to 62.71kg of a first polymer template latex at a constant speed under a temperature condition of 60-65°C by means of a starvation polymerization method; after the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material inlaid with silicon dioxide particles with a particle size of 20nm-30nm is coated on the surface of the polyacrylamide latex particles, thereby obtaining a second polymer template latex having a bayberry-like multilayer core-shell structure;

[0086] 10 kg of ammonium polyphosphate, 0.7 kg of ethanol and 5 kg of deionized water are used to prepare a third mixed solution; by means of an ion exchange reaction, 15.7 kg of the third mixed solution is added dropwise to 101.855 kg of the second polymer template emulsion at a constant speed at a temperature of 30 to 40° C., stirred at a stirring speed of less than 80 r / min, and refluxed and condensed for 4 hours under this temperature condition to obtain a third polymer template emulsion with a multilayer core-shell structure having linear ammonium polyphosphate as the outermost branch chain;

[0087] A fourth mixed solution is prepared by using 10 kg of glycidyl methacrylate, 0.15 kg of an initiator, and 7.5 kg of deionized water; by using a starvation polymerization method, 17.65 kg of the fourth mixed solution is added dropwise to 117.555 parts by weight of a third polymer template latex at a constant speed under a temperature condition of 60 to 65° C., and stirred at a stirring speed of less than 80 r / min, and refluxed and condensed under this temperature condition for 3 hours to form a second polymer with linear polymethacrylate glycidyl as a branch chain on the surface of the latex particles, thereby obtaining polyacrylamide-based organic / inorganic composite latex particles having a "sea buckthorn"-shaped multilayer core-shell structure and being multiply cross-linkable;

[0088] 3 kg of carbonizing agent, 0.5 kg of rheological additive and 20 kg of deionized water were mixed, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and then aged for 12 hours to obtain a transparent, dynamically reversible gel material;

[0089] 135.205 kg of polyacrylamide-based organic / inorganic composite latex particles with a "roxburgh"-shaped multilayer core-shell structure and multiple cross-linking and 3 kg of cellulose solvent are mixed, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to form a uniform suspension; 23.5 kg of a transparent, dynamically reversible gelling material is added thereto, and stirred at a stirring speed of less than 80 r / min for 80 minutes at room temperature to obtain a clear or slightly turbid pre-reaction liquid; 1.5 kg of a catalyst and 0.02 kg of a defoaming agent are added to the pre-reaction liquid in sequence, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to obtain a fire-proof pre-reaction liquid, which is left to stand for use;

[0090] In accordance with the standard requirements of XF 159-2011 "Water-based flame retardants", the fire-retardant pre-reaction liquid is sprayed onto the surface of the transparent cellulose-modified soda-lime glass product, left to stand for 50 minutes, and after the surface of the glass product is dry, it is placed in a 50°C oven and baked for 4 hours, and then heated to 80°C and baked for 3 hours, so that the cellulose on the glass surface and the fire-retardant pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure, thereby improving the flame retardant properties of the product.

[0091] Example 2

[0092] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0093] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0094] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of 20wt% ammonia water, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 8.5kg of ammonium polyphosphate, 8.5kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0095] (2) The above raw materials were used to prepare polyacrylamide-based organic / inorganic hybrid nanomaterials according to the same preparation method as in Example 1.

[0096] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0097] Example 3

[0098] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0099] The polyacrylamide-based organic / inorganic hybrid nanomaterial in this embodiment is prepared by the following steps:

[0100] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0101] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of ammonia water with a concentration of 20wt%, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 7kg of ammonium polyphosphate, 7kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0102] (2) The above raw materials were used to prepare polyacrylamide-based organic / inorganic hybrid nanomaterials according to the same preparation method as in Example 1.

[0103] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0104] Example 4

[0105] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0106] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0107] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of ammonia water with a concentration of 20wt%, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 5.5kg of ammonium polyphosphate, 5.5kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0108] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.

[0109] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0110] Example 5

[0111] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0112] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0113] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of ammonia water with a concentration of 20wt%, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 11.5kg of ammonium polyphosphate, 11.5kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0114] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.

[0115] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0116] Example 6

[0117] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0118] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0119] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of 20wt% ammonia water, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 13kg of ammonium polyphosphate, 13kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0120] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.

[0121] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0122] Example 7

[0123] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0124] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0125] 2.3kg of tetraethyl orthosilicate, 0.03kg of concentrated ammonia water with a concentration of 25wt%, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of ammonia water with a concentration of 20wt%, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.4kg of rheological additive, 2.75kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoamer. (2) Prepare a fire-proof pre-reaction liquid by the same preparation method as in Example 1.

[0126] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0127] Example 8

[0128] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0129] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0130] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of 20wt% ammonia water, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.3kg of rheological additive, 2kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0131] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.

[0132] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0133] Example 9

[0134] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0135] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0136] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of 20wt% ammonia water, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.2kg of rheological additive, 1.25kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0137] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.

[0138] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0139] Example 10

[0140] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0141] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0142] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.025kg of divinyl sulfone, 0.1kg of 20wt% ammonia water, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.2kg of rheological additive, 1.25kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0143] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.

[0144] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0145] Embodiment 11

[0146] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0147] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0148] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.015kg of divinyl sulfone, 0.1kg of 20wt% ammonia water, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.2kg of rheological additive, 1.25kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0149] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.

[0150] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0151] Example 12

[0152] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:

[0153] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:

[0154] 2.3kg of tetraethyl orthosilicate, 0.03kg of 25wt% concentrated ammonia water, 55kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.71kg of ethanol, 40kg of polyacrylamide solution, 7kg of butyl acrylate, 2kg of methyl methacrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of 20wt% ammonia water, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 2kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.055kg of emulsifier, 0.22kg of initiator, 3kg of carbonizing agent, 0.2kg of rheological additive, 1.25kg of cellulose solvent, 1.0kg of catalyst, and 0.02kg of defoaming agent.

[0155] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.

[0156] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0157] Comparative Example 1

[0158] This comparative example provides a fire-proof pre-reaction liquid, whose raw materials are 55kg of deionized water, 3kg of melamine, 4kg of 2,4-methyl-3-cyclohexene formaldehyde, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.05kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.

[0159] The preparation method of the fire-proof pre-reaction liquid in this comparative example is the same as the preparation method of the fire-proof pre-reaction liquid in Example 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0160] Comparative Example 2

[0161] This comparative example provides a fire-proof pre-reaction liquid, whose raw materials are 55kg of deionized water, 3kg of melamine, 4kg of 2,4-methyl-3-cyclohexene formaldehyde, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.05kg of initiator, 1.5kg of catalyst, and 0.02kg of defoamer.

[0162] The preparation method of the fire-proof pre-reaction liquid in this comparative example is the same as the preparation method of the fire-proof pre-reaction liquid in Example 1, except that the composition of the fire-proof pre-reaction liquid is different.

[0163] Comparative Example 3

[0164] This comparative example is a transparent cellulose-modified soda-lime glass product that has not been flame-retardant treated.

[0165] According to the standard requirements of XF 159-2011 "Water-based Flame Retardant", the flame retardant performance test was conducted on the glass samples coated with the fire-retardant pre-reaction liquid provided in Examples 1 to 12 and Comparative Examples 1 to 3. Four parallel samples were taken in the experiment, and the average value of the data was taken as the experimental result; the viscosity of the fire-retardant pre-reaction liquid was measured according to the GB / T1723 coating viscosity determination method; and the apparent quality of each wooden product was obtained by naked eye observation. The performance parameters of the fire-retardant pre-reaction liquid prepared in the examples of the present invention and the comparative examples are shown in Table 1.

[0166] Table 1 Performance parameters of fire retardant pre-reaction liquid

[0167]

[0168]

[0169] As can be seen from Table 1, the fireproof pre-reaction liquid in the present invention has a long fireproof time and water-resistant after solidification, while the fireproof layer formed by the fireproof pre-reaction liquid prepared in the comparative example does not have the characteristics of water-resistant; the fireproof time formed by the fireproof pre-reaction liquid in the present invention after solidification is 1.5-7 times that of the comparative example, and the hardness and ultraviolet radiation resistance time are also significantly higher than those of the comparative example. The above description uses only 2,4-methyl-3-cyclohexene melamine formaldehyde resin and ammonium polyphosphate as fireproof materials, which are easily washed away during water flushing, seriously affecting the safety of glass windows. The present invention improves the formula of the fireproof pre-reaction liquid, adopts polyacrylamide-based organic / inorganic composite latex particles with a "thorn pear"-shaped multi-layer core-shell structure and a multi-crosslinkable core-shell structure and is mixed with an additive, and a synergistic effect is generated between the components of the fireproof pre-reaction liquid, thereby improving the flame retardant properties of the material, especially after water flushing, the flame retardant properties of the glass product are still unaffected, and at the same time, the low temperature resistance of the fireproof layer formed after the fireproof pre-reaction liquid is cured is also improved, and it can be used in low temperature (-25℃±1℃) and outdoor environment. The fireproof pre-reaction liquid prepared by the embodiment of the present invention has the advantages of low viscosity, high hardness, good adhesion, long flame retardant time, low temperature resistance and ultraviolet radiation resistance, and can form a transparent coating when applied on the surface of an object.

[0170] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0171] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. Polyacrylamide-based organic / inorganic hybrid nanomaterial, characterized in that: The invention comprises polyacrylamide-based organic / inorganic composite latex particles, wherein the polyacrylamide-based organic / inorganic composite latex particles comprise a flexible core layer, a functional shell layer and a reinforcing transition layer, wherein the reinforcing transition layer is arranged between the flexible core layer and the functional shell layer; the functional shell layer is a polymer layer inlaid with surface-modified hydrophilic silica nanoparticles and comprising a phosphorus-containing polymer and a silicon-containing polymer, and at least one of the polymers in the functional shell layer is a polymer that can form an interpenetrating network structure with cellulose, and in the functional shell layer, one end of linear ammonium polyphosphate and one end of linear poly(glycidyl methacrylate) are respectively grafted on the surface-modified hydrophilic silica nanoparticles, and the other end of the linear ammonium polyphosphate and the other end of the linear poly(glycidyl methacrylate) are respectively grafted on the surface-modified hydrophilic silica nanoparticles. The other end is respectively located outside the shell of the functional shell layer, the surface modification is to introduce an alkenyl silane coupling agent and an amino silane coupling agent on the surface of the water-based silica nanoparticles; the reinforcing transition layer is a polymer layer containing a melamine formaldehyde material with a cross-linked network structure; the flexible core layer is polyacrylamide latex particles; the polyacrylamide-based organic / inorganic hybrid nanomaterial is made of the following components: 10 to 25 parts by weight of the fourth mixed solution and 58 to 352 parts by weight of the third polymer template solution; the fourth mixed solution is mixed with 5 to 15 parts by weight of glycidyl methacrylate, 0.01 to 0.2 parts by weight of an initiator and 5 to 10 parts by weight of deionized water; the third polymer template solution is mixed with 7 to 26 parts by weight of the third mixed solution; The first polymer template emulsion is prepared by mixing a first mixed solution and 51 to 326 parts by weight of a second polymer template emulsion; the third mixed solution is prepared by mixing 5 to 15 parts by weight of ammonium polyphosphate, 0.5 to 1 part by weight of ethanol and 2 to 10 parts by weight of deionized water; the second polymer template emulsion is prepared by mixing 0.3 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silicon dioxide dispersion with double bonds and amine groups on the surface, 0.003 to 0.03 parts by weight of an initiator, and 26 to 242 parts by weight of a first polymer template emulsion; the second mixed solution is prepared by mixing 0.1 to 6 parts by weight of butyl acrylate, 0.1 to 6 parts by weight of methyl methacrylate, 0.1 to 6 parts by weight of methacrylic acid and 0.01 to 0.02 parts by weight of methyl methacrylate. The first polymer template emulsion is made of 0.5-80 weight parts of the first mixed solution, 6-12 weight parts of deionized water, 0.005-1 weight parts of initiator and 20-150 weight parts of polyacrylamide emulsion with a particle size of 40nm-200nm and a solid content of 15wt%-55wt%; the first mixed solution is made of 0.1-20 weight parts of butyl acrylate, 0.1-20 weight parts of melamine, 0.1-20 weight parts of styrene, 0.01-0.03 weight parts of divinyl sulfone, 0.05-0.2 weight parts of 20wt% ammonia water, 0.1-20 weight parts of 2,4-methyl-3-cyclohexene carboxaldehyde and 0.002-0.0.08 weight parts of reactive emulsifier; hydrophilic silica dispersion with double bonds and amine groups on the surface is made of 10-25 weight parts of silica seed solution, 0.1-0.5 weight parts of alkenyl silane coupling agent, 0.1-0.5 weight parts of amino silane coupling agent and 0.001-0.02 weight parts of ethanol; silica seed solution is made of 2-3 weight parts of ethyl orthosilicate, 0.02-0.04 weight parts of 25wt% concentrated ammonia water and 8-22 weight parts of deionized water. .

2. The polyacrylamide-based organic / inorganic hybrid nanomaterial according to claim 1, characterized in that: The polymerization degree of the polyacrylamide particles in the polyacrylamide emulsion is 10000-100000, the particle size is 40nm-200nm, and the particle size distribution is a single peak narrow distribution.

3. The polyacrylamide-based organic / inorganic hybrid nanomaterial according to claim 1, characterized in that: The alkenyl silane coupling agent is one or more of vinyl triperoxide tert-butyl silane, vinyl triethoxy silane, butadienyl triethoxy silane, vinyl trimethoxy silane, isobutylenyl triethoxy silane and vinyl tri(β-methoxyethoxy) silane; the amino silane coupling agent is one or more of anilinomethyl triethoxy silane, γ-aminopropyl trimethoxy silane, N-β(aminoethyl)-γ-aminopropyl triethoxy silane and 3-aminopropyl triethoxy silane; and the initiator is one or both of a thermal initiator and a redox initiator.

4. The method for preparing the polyacrylamide-based organic / inorganic hybrid nanomaterial according to claim 1, characterized in that: The steps include: S11) preparing a silicon dioxide seed solution: mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3: 0.02-0.04: 8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm to 30 nm; S12) preparing a silica dispersion with double bonds and amine groups on the surface: placing a silica seed solution, an alkenyl silane coupling agent, an amine silane coupling agent and ethanol in a weight ratio of 10-25:0.1-0.5:0.1-0.5:0.001-0.02 in a high-pressure homogenizer for circulation dispersion for 10 minutes, placing the mixture in a three-necked flask, and then placing the three-necked flask in a water bath at 70°C-90°C, stirring and dispersing at a stirring speed of 100-150 r / min for 30 minutes, and then cooling to 20°C to obtain a silica dispersion with double bonds and amine groups on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11); S13) preparing a first polymer template emulsion, the specific steps are as follows: S13-1) mixing butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt% ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and a reactive emulsifier in a weight ratio of 0.1-20: 0.1-20: 0.1-20: 0.01-0.03: 0.05-0.2: 0.1-20: 0.002-0.08 to prepare a first mixed solution; S13-2) By means of starvation polymerization, 0.5 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water and 0.005 to 1 part by weight of an initiator are added dropwise to 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt% at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion having a cross-linked core-shell structure; S14) preparing a second polymer template emulsion, the specific steps are as follows: S14-1) mixing butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier in a weight ratio of 0.1-6: 0.1-6: 0.1-6: 0.01-0.02 to prepare a second mixed solution; S14-2) By means of starvation polymerization, 0.3 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silica dispersion having double bonds and amine groups on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 242 parts by weight of a first polymer template latex at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material embedded with silica particles having a particle size of 20 nm to 30 nm is coated on the surface of the polyacrylamide latex particles, thereby obtaining a second polymer template latex having a bayberry-like multilayer core-shell structure; S15) preparing a third polymer template latex, the specific steps are as follows: S15-1) ammonium polyphosphate, ethanol and deionized water are mixed in a weight ratio of 5-15: 0.5-1: 2-10 to prepare a third mixed solution; S15-2) by means of an ion exchange reaction, at a temperature of 30 to 40° C., 7 to 26 parts by weight of the third mixed solution are added dropwise to 51 to 326 parts by weight of the second polymer template emulsion at a constant speed, stirred at a stirring speed of less than 80 r / min, and refluxed and condensed for 4 hours under this temperature condition to obtain a third polymer template emulsion having a multilayer core-shell structure with linear ammonium polyphosphate as the outermost branch chain; S16) preparing organic / inorganic composite latex particles, the specific steps are as follows: S16-1) preparing a fourth mixed solution by mixing glycidyl methacrylate, an initiator and deionized water in a weight ratio of 5-15: 0.01-0.2: 5-10; S16-2) Add 10 to 25 parts by weight of the fourth mixed solution to 58 to 352 parts by weight of the third polymer template latex at a constant speed at a temperature of 60 to 65°C, stir at a stirring speed lower than 80 r / min, and reflux and condense for 3 hours at this temperature to form a second polymer with linear poly(glycidyl methacrylate) as a branch on the surface of the latex particles, and obtain organic / inorganic composite latex particles with a "sea buckthorn"-shaped multilayer core-shell structure and multiple cross-linking, that is, obtain polyacrylamide-based organic / inorganic hybrid nanomaterials.

5. A fire-proof pre-reaction liquid, characterized in that: The invention comprises at least the following components: 68 to 377 parts by weight of polyacrylamide-based organic / inorganic hybrid nanomaterial, 0.5 to 4 parts by weight of cellulose solvent, 0.5 to 2.5 parts by weight of catalyst and 10 to 30 parts by weight of deionized water; wherein the polyacrylamide-based organic / inorganic hybrid nanomaterial is the polyacrylamide-based organic / inorganic hybrid nanomaterial according to claim 1.

6. The fire-proof pre-reaction liquid according to claim 5, characterized in that: It also includes 1 to 5 parts by weight of a carbonizing agent, 0.001 to 0.05 parts by weight of a defoaming agent and 0.1 to 1 parts by weight of a rheological aid; the carbonizing agent is compounded from one or more of sucrose, fructose, glucose and maltose with pentaerythritol, wherein the proportion of pentaerythritol in the carbonizing agent is greater than or equal to 25wt%; the rheological aid is one or more of hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose; the cellulose solvent is one or more of dipropylene glycol methyl ether and N-methyl morpholine oxide; the catalyst is compounded from a hydrochloric acid solution with a mass percentage less than or equal to 20% and one or two of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite, wherein the hydrochloric acid solution accounts for less than or equal to 90wt% of the catalyst; the defoaming agent is one or two of a polysiloxane defoaming agent and a polyether defoaming agent.

7. The method for preparing the fire-proof pre-reaction liquid according to claim 6, characterized in that: The steps include: S21), mixing a carbonizing agent, a rheological additive, and deionized water in a weight ratio of 1-5: 0.1-1: 10-25, stirring at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and aging for 12 hours to obtain a transparent and dynamically reversible gel material; S22) Mix polyacrylamide-based organic / inorganic hybrid nanomaterials and cellulose solvent in a weight ratio of 68-377:0.5-4, and stir at a stirring speed of less than 80 r / min for 40 minutes at room temperature to form a uniform suspension; then add 11-30 parts by weight of gelling material thereto, and stir at a stirring speed of less than 80 r / min for 80 minutes at room temperature to obtain a pre-reaction liquid; then add 0.5-2.5 parts by weight of a catalyst and 0.001-0.05 parts by weight of a defoaming agent to the pre-reaction liquid in sequence, and stir at a stirring speed of less than 80 r / min for 40 minutes at room temperature to obtain a fire-retardant pre-reaction liquid, which is allowed to stand for use.

8. The use of the fire-proof pre-reaction liquid according to claim 5, characterized in that: It is used for flame retardant treatment of transparent cellulose modified soda-lime glass products and forms a fireproof layer with a thickness of 0.02-0.3mm on the surface of the glass products. The specific operation is: spray the fireproof pre-reaction liquid onto the surface of the transparent cellulose modified soda-lime glass product, let it stand for 50 minutes, and after the surface of the glass is dry, put it into a 50℃ oven for baking for 4 hours, and then heat it to 80℃ and bake for 3 hours, so that the cellulose on the glass surface and the fireproof pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure.

Citation Information

Patent Citations

  • Silica sol / polyacrylic ester emulsion with high silicon content and preparation method of silica sol / polyacrylic ester emulsion

    CN104530302A

  • Polylactic acid-based organic / inorganic hybrid nano-material, fireproof pre-reaction liquid, and preparation method and application of fireproof pre-reaction liquid

    CN117264137A